Landlords and tenants in imperial Rome - Frier, Bruce W., 1943- (Princeton University Press, 1980)
By examining a portion of private law in imperial Rome as a functioning element in social life, this book constitutes an important contribution to the sociological understanding of law in premodern societies. Using archaeological data as well as literary and legal texts, Bruce Frier shows that members of the upper class, including senatorial families, lived in rented apartments and that the Roman law of urban lease was designed mainly for them, not for the lower class. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.